Nursing Science Journal of Thailand Index 2019 - Sirorojsakul, Surang; Dechosawang, Siripen; Dacha, Nipaporn (Nursing Science Journal of Thailand, 2019)
Subject Index A Abdomen – surgery Thuchart, S. and others. “The effects of concreteobjective information program on pre-operative anxiety in abdominal surgery patients” Nurs Sci J Thail. 2019 ; Apr.-Jun. ; 37(2):78-91. Achievement motivation Srihabutr, S. and Krainuwut, P. “Factors predicting quality of care among patients with diabetes at public health centers, Bangkok metropolitan administration” Nurs Sci J Thail. 2019 ; Apr.-Jun. ; 37(2):92-106. Acute coronary syndrome Tomon, S. and others. “The influences of anxiety, attitudes, beliefs, and knowledge about symptoms on decision-making time in seeking treatment in patients with acute coronary syndrome” Nurs Sci J Thail. 2019 ; Apr.-Jun. ; 37(2):60-77. Adolescence Chanphong, J. “Parent-child sexual communication” Nurs Sci J Thail. 2019 ; Jan.-Mar. ; 37(1):4-16. Suwanchinda, P. and Suttharangsee, W. “Development and psychometric evaluation of intention to drugs avoidance scale (IDAS) for thai adolescents” Nurs Sci J Thail. 2019 ; Jul.-Sep. ; 37(3):4-17. Aged Rodcharoen, S. and Kongsuwan, V. “The effects of self-guided cognitive behavioral modification program on self-esteem and depression of elders with major depressive disorder” Nurs Sci J Thail. 2019 ; Jul.-Sep. ; 37(3):91-106. Seesawang, J. and Thongtang, P. “Factors associated with self-management ability among older adults with hypertension in Asia: a systematic review of qualitative studies” Nurs Sci J Thail. 2019 ; Jan.-Mar. ; 37(1):86-107. Anxiety Thuchart, S. and others. “The effects of concreteobjective information program on pre-operative anxiety in abdominal surgery patients” Nurs Sci J Thail. 2019 ; Apr.-Jun. ; 37(2):78-91.